2020
DOI: 10.5114/aoms.2018.81128
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of the hospital nutrition screening tool CIPA

Abstract: A b s t r a c t Introduction: Hospital malnutrition is very common and worsens the clinical course of patients while increasing costs. Lacking clinical-economic studies on the implementation of nutrition screening encouraged the evaluation of the CIPA (Control of Food Intake, Protein, Anthropometry) tool. Material and methods: An open, non-randomized, controlled clinical trial was conducted on patients admitted to internal medicine and general and digestive surgery wards, who were either assigned to a control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The benefits of physical activity in cancer patients are multifaceted; they have been observed in cancer prevention, mortality, and quality of life [24]. Thus, the majority of studies included exercise as a therapy to decrease BCRL symptoms; however, few studies suggest a preventive approach to the disease [18][19][20][21][22][23][24][25]. Based on the obvious need to develop preventive measures, the aim of the present review was to determine the efficacy of therapeutic exercise in the prevention of lymphoedema evaluated through cirtometry, volumetry, or bioimpedance spectroscopy (BIS) of the upper limb (UL) in women after breast cancer removal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of physical activity in cancer patients are multifaceted; they have been observed in cancer prevention, mortality, and quality of life [24]. Thus, the majority of studies included exercise as a therapy to decrease BCRL symptoms; however, few studies suggest a preventive approach to the disease [18][19][20][21][22][23][24][25]. Based on the obvious need to develop preventive measures, the aim of the present review was to determine the efficacy of therapeutic exercise in the prevention of lymphoedema evaluated through cirtometry, volumetry, or bioimpedance spectroscopy (BIS) of the upper limb (UL) in women after breast cancer removal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…computer programs supported by artificial intelligence (AI)) for analysis of the nutrition of patients and for assessment of the use of nutritional interventions. What is more, the tools introduced to support nutritional work are not always economically beneficial [ 1 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The detailed study protocol and cost-effectiveness analysis have been published elsewhere (the overall study included patients admitted to internal medicine as well as surgical patients). Here, we present the clinical outcomes observed in surgical patients [21,22].…”
Section: Methodsmentioning
confidence: 99%
“…Assuming that such implementation would improve clinical variables and cost-effectiveness, a secondary objective was to promote the use of nutrition screening in other hospitals. Evaluating the economic aspect, we observed that, in addition to improving quality-adjusted life years, the implemented CIPA screening in surgical patients did save costs compared to usual clinical practices [22]. This work presents all the clinical findings in these patients in detail.…”
Section: Introductionmentioning
confidence: 99%